Attachment-Based Clinical Work with Children and Adolescents - Bettmann, Joanna Ellen; Demetri Friedman, Donna; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
It is hard to imagine child psychology without the work of John Bowlby: his insights into children$1 (Bs relational experience have left a major impact across the mental health professions. But of all these fields, clinical work with children$1 (Bwhich deals so much with the consequences of faulty attachment$1 (Bseems to have the most affinity with Bowlby$1 (Bs observations. Attachment-Based Clinical Work with Children and Adolescents assembles current theory and findings on attachment, applies them to clinical work with diverse youth populations, and offers valid ideas for building an attachment framework in practice. This volume covers the spectrum of attachment-oriented practice throughout the country with infants, toddlers, grade-schoolers, and teens in individual, family (including adoptive and foster families), and group settings. The novel interventions illustrated here, with their therapeutic and training implications, show attachment-oriented clinical work as evolving, relevant, open to multidisciplinary collaboration, and highly effective in repairing relationship damage in vulnerable youngsters. A sampling of the coverage: How mother-infant research informs attachment-based clinical practice. Using modern attachment theory to guide clinical assessment of early attachment relationships. An attachment-based video intervention in a community mental health center. The essential role of the body in the parent-infant relationship. Peer-play psychotherapy enhancing development among young children. Implementing attachment theory in the child welfare system. Attachment-Based Clinical Work with Children and Adolescents is a groundbreaking resource for mental health professionals, academicians, and graduate students.s
Introduction -- I. ATTACHMENT THEORY AND RESEARCH WITH CHILDREN -- Observing development: A comparative view of attachment theory and separation-individuation theory -- Securing attachment: Mother-infant research informs attachment-based clinical practice -- Using modern attachment theory to guide clinical assessments of early attachment relationships. II. ATTACHMENT-BASED CLINICAL WORK WITH CHILDREN AND ADOLESCENTS -- Becoming baby watchers: An attachment-based video intervention in a community mental health center -- Trauma focused child-parent psychotherapy in a community pediatric clinic: A cross-disciplinary collaboration -- he essential role of the body in the parent-infant relationship: Non-verbal analysis of attachment -- Gems hidden in plain sight: Peer-play psychotherapy nourishes relationships and growth across developmental domains among young children -- The impact of intervention points of entry on attachment-based processes of therapeutic change with prepubertal children -- Attachment processes in wilderness therapy settings -- III. BUILDING CAPACITY FOR ATTACHMENT-BASED CLINICAL WORK -- From out of sight, out of mind to in-sight and in mind: Enhancing reflective capacities in a group attachment-based intervention -- Implementing attachment theory in the child welfare system: Clinical implications and organizational considerations.
Keywords: Social sciences; Social policy; Social work; Developmental psychology; Social Sciences; Social Work; Child and School Psychology; Family; Social Policy